A case report about focal status epilepticus as first presentation in Alzheimer’s disease: finding the culprit - Astrid Devulder; Greet Vanderlinden; Evy Cleeren; Valerie Goovaerts; Tom Theys; Koen Van Laere; Wim Van Paesschen (BMC Neurology)
Abstract Background Neuronal hyperexcitability has been proposed to play a key role in Alzheimer’s disease (AD). Understanding the relation between this enhanced excitability and AD pathology could provide a window for therapeutic interventions. However epileptiform activity is often subclinical, hidden on scalp EEG and very challenging to assess with current diagnostic modalities. Case presentation A woman in her sixties presented with acute confusion. Despite a normal scalp electroencephalogram (EEG), magnetic resonance imaging (MRI) showed cytotoxic edema of the right mesial temporal lobe and hippocampal hypermetabolism was present on ([18F]-fluoro-2-deoxyglucose positron emission tomography (PET). Bilateral foramen ovale (FO) electrodes were placed to directly record mesial temporal activity and revealed continuous mesial temporal epileptic activity, while scalp EEG remained normal. After recovery, a new diagnosis of AD was established on cerebrospinal fluid. The lateralization of the epileptiform activity was congruent with the predominant side of tau pathology in the mesial temporal cortex on 18F-MK6240 PET. On follow-up MRI, two and five months later, the right hippocampus became atrophic. Conclusion This case highlights the significant role of neuronal hyperexcitability in early AD pathogenesis and how shared mechanisms between AD and epilepsy can complicate clinical management.